2019
DOI: 10.3389/fnins.2019.01164
|View full text |Cite
|
Sign up to set email alerts
|

Re-weighting of Sound Localization Cues by Audiovisual Training

Abstract: Sound localization requires the integration in the brain of auditory spatial cues generated by interactions with the external ears, head and body. Perceptual learning studies have shown that the relative weighting of these cues can change in a context-dependent fashion if their relative reliability is altered. One factor that may influence this process is vision, which tends to dominate localization judgments when both modalities are present and induces a recalibration of auditory space if they become misalign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 74 publications
2
17
0
Order By: Relevance
“…It is well known that the normal auditory system not only combines ITD information with ILD and monaural spectral cues to localize sounds in space, it also adapts strongly to changes in these cues, and can re-weight them depending on their reliability ( Keating et al, 2013b ; Keating et al, 2015 ; Tillein et al, 2016 ; Kumpik et al, 2019 ). Similarly, Jones et al, 2011 demonstrated changes in ITD and ILD thresholds as head size and pinnae grow for up to 6 weeks postnatally in chinchillas.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the normal auditory system not only combines ITD information with ILD and monaural spectral cues to localize sounds in space, it also adapts strongly to changes in these cues, and can re-weight them depending on their reliability ( Keating et al, 2013b ; Keating et al, 2015 ; Tillein et al, 2016 ; Kumpik et al, 2019 ). Similarly, Jones et al, 2011 demonstrated changes in ITD and ILD thresholds as head size and pinnae grow for up to 6 weeks postnatally in chinchillas.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with Rakerd and Hartmann's (2010) observation that responses follow ILDs in reverberant environments. Furthermore, Kumpik et al (2019) found an even stronger increase in ILD weighting for a condition in which no cue was randomized (i.e., spatially consistent ITDs and ILDs were presented), making it difficult to draw strong conclusions. Considering the changing relative contributions of ITD and ILD depending on stimulus and contextual factors as discussed above, binaural-cue reweighting likely plays a role in adapting to variable acoustic environments.…”
Section: Introductionmentioning
confidence: 98%
“…Potential reasons for their null result are that (1) the training regimen (i.e., left/ right discrimination) was not sufficiently intuitive, (2) the stimuli were noise bands centered at 500 Hz and thus in a frequency range where only ITDs but not ILDs arise naturally (except for sound sources near the head), (3) the binaural cues used were not sufficiently salient as they were close to the binaural-cue threshold, and (4) auditory and visual stimuli were not presented simultaneously, preventing bottom-up multisensory integration that may be required to induce reweighting. Kumpik et al (2019) presented auditory stimuli with either randomized ITDs (and stable ILDs) or randomized ILDs (and stable ITDs) while participants completed a visual oddball task. They observed an increase in ILD weighting after ITDs were randomized, but no increase in ITD weighting after ILDs were randomized.…”
Section: Introductionmentioning
confidence: 99%
“…i.e., binaural hearing, humans and animals are able to localize a sound source not only in a 2D space, but also in a three-dimensional (3D) space by analyzing different auditory cues. The brain deciphers the audio cues to predict the direction and distance of the sound source [ 3 ]. The job of the ears is to capture and send natural acoustic signals to the brain for processing.…”
Section: Introductionmentioning
confidence: 99%